2021
DOI: 10.1021/acs.orglett.1c04017
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Sulfonium-Promoted Peptide and Protein Amidation in Aqueous Media

Abstract: A novel amidation strategy using electrophilic sulfonium, which is soluble and stable in aqueous conditions, was developed. The sulfoniums could activate thioacid and carboxyl acid to efficiently react with amines to afford amides. This method enables applications in amidation in both aqueous media and solid-phase peptide synthesis, peptide/protein modifications, and reactive lysines of a proteome at pH 10 with activity-based protein profiling. A peptide ligand-directed labeling of the USP7–UBL2 domain was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…Inspired by the allenone coupling reagent, Li et al reported that propargyl sulfoniums, which have similar behavior to that of allenones under basic conditions, could also act as a coupling reagent. 236 They had been successfully applied to peptide synthesis and protein amidation. The mechanistic study indicated that the active thioesters prepared by the addition of thioacids and propargyl sulfoniums are the key intermediates, which could be applied in SPPS and protein labeling studies (Scheme 55).…”
Section: Active Esters Formed Upon Reaction With Activating Reagentsmentioning
confidence: 99%
“…Inspired by the allenone coupling reagent, Li et al reported that propargyl sulfoniums, which have similar behavior to that of allenones under basic conditions, could also act as a coupling reagent. 236 They had been successfully applied to peptide synthesis and protein amidation. The mechanistic study indicated that the active thioesters prepared by the addition of thioacids and propargyl sulfoniums are the key intermediates, which could be applied in SPPS and protein labeling studies (Scheme 55).…”
Section: Active Esters Formed Upon Reaction With Activating Reagentsmentioning
confidence: 99%
“…[59] Subsequently, the activity of Yanmides in the synthesis of thioamides/primary thioamides, [60] thiopeptides bond, [61] α-Ketoamides, [62] lactam and peptide fragment condensation [63] were further explored. Apart from the abovementioned ynamide-type coupling reagents, other triple bondcontaining reagents, including methyl propiolate (99, Figure 2, Scheme 19c) [64] and dimethyl dimethyl(prop-2-yn-1yl)sulfonium bromide (Yin, Wang & Li, 2022, Figure 2, Scheme 19d), [65] were also recently developed and applied to the field of SPPS.…”
Section: Direct Amidation Of Carboxylic Acids With Amines Promoted By...mentioning
confidence: 99%
“…6 Diverse bioconjugation technologies have been developed to achieve chemo-and site-selective functionalization of natural amino acids (AAs) for the purpose of selective protein modication. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] The low abundance and unique reactivity of the thiol side chain of cysteine (Cys) make it an ideal candidate for bioconjugation chemistry. [21][22][23][24][25][26][27][28][29][30][31][32][33] Michaeltype addition, nucleophilic substitution and disulde exchange reaction represent the classical approaches for Cys-selective bioconjugation (Fig.…”
Section: Introductionmentioning
confidence: 99%